Digitalization of the Russian System for Assessing the Quality of General Education: Results and Prospects - Jeanne S. VASILIEVA; Anton K. KUZNETSOV (Communications of International Proceedings, 2021)
One of the main priorities of the Russian national educational policy is the construction and development of a unified system for assessing the quality of education, including independent objective forms of grading and control. The integration of digital technologies and tools into this system is induced not only by the governmentally set tasks, but also by the complexity of the system itself, a significant number of stakeholders with different information requests, the need to organize prompt feedback between the participants of the processes, a variety of heterogeneous interrelated objects, etc. The research studies the processes of digitalization in the context of the main elements of the system for assessing the general education's quality: the unified state examination, the basic state examination, the national study of the quality of education, the all-Russia tests, international comparative studies of the quality of education, studies of teachers' professional competence, control and supervisory activities. The successes in modernization of assessment procedures are noted and the prospects for their development are given. The study also presents recommendations for further improvement of the unified system for assessing the quality of education.
Keywords: Quality of Education; Unified System for Assessing the Quality of Education; Assessment of The General Education's Quality; Unified State Examination (USE); National Studies on The Quality of Education; All-Russia Test Papers.